Maintenance management practiced by corporate companies / Mohd Hizuddin Yusoff @ Hashim - Yusoff @ Hashim, Mohd Hizuddin (2009)
Management is essential in daily life. It's fundamental in everything. Without good management, it's not easy to achieve the desired result from efforts. Good management will lead to the best result.